2022
DOI: 10.1039/d2ra02214a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous-rich calcium and potassium-activated carbons prepared from degreased spent coffee grounds for efficient removal of MnO42− in aqueous media

Abstract: Spent coffee grounds are an interesting high volume renewable resource for valorisation. Activation with CaCl2 produces mesoporous carbons with high capacity for removal of MnO42−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…36 Bose et al produced coffee-ground-derived ACs by ZnCl 2 activation and obtained a very low S BET of 684 m 2 g −1 and total pore volume of 0.526 cm 3 g −1 compared to those reported in other studies. 37 As evident from the aforementioned studies, although corrosive chemical activating agents have been mostly used for synthesizing well-developed microporous carbons, these ACs still exhibit moderate textural features. However, in our study, we obtained the highest S BET of 2156 m 2 g −1 and a superior V total of 1.076 cm 3 g −1 for CAC4.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…36 Bose et al produced coffee-ground-derived ACs by ZnCl 2 activation and obtained a very low S BET of 684 m 2 g −1 and total pore volume of 0.526 cm 3 g −1 compared to those reported in other studies. 37 As evident from the aforementioned studies, although corrosive chemical activating agents have been mostly used for synthesizing well-developed microporous carbons, these ACs still exhibit moderate textural features. However, in our study, we obtained the highest S BET of 2156 m 2 g −1 and a superior V total of 1.076 cm 3 g −1 for CAC4.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…Compared with other mesoporous particles, the pore size of ordered mesoporous carbon (OMC) is more uniform, and the distribution and arrangement of mesoporous carbon are more regular [43][44][45][46]. OMC is often used to design electrochemical signal amplifiers or immune signal sensors for biological detection, due to the electrical conductivity of regularly arranged carbon atoms [47,48].…”
Section: Ordered Mesoporous Carbonmentioning
confidence: 99%
“…It has been reported that these methods can have a negative impact on the environment, releasing contaminating residues of tannin, caffeine and polyphenols [33]. Other ways of valorizing SCGs have been proposed, such as converting them into biofuel, biodiesel, bioethanol or biomaterials [34] and producing biochar and AC [35][36][37]. These routes can help reinforce the circular economy approach by enabling continuous processes that reduce the accumulation of waste by transforming it into useful, value-added materials while promoting more environmentally friendly models [38,39].…”
Section: Introductionmentioning
confidence: 99%